A combination of maternal and paternal features discriminates between children with secure and insecure attachment style - Antonucci, Linda A. (2022)
Child-caregiver attachment security has been associated with positive developmental outcomes. However, many aspects related to the parenting environment, besides attachment organization, should be considered in the prediction of offspring’s attachment. We aimed at building an ecological classification model of child attachment based on many variables related to the individual and dyadic features of both parents. Having recruited 150 families, we fed a stepwise logistic regression analysis, aimed at discriminating between secure and insecure child attachment. This contained information regarding parental stress, parental avoidance and anxiety in romantic relationships, quality of the romantic relationship and parental involvement. Paternal responsibility, paternal perception of the quality of the romantic relationship and maternal attachment avoidance were the most discriminative variables in the model (all p<.05). Findings support the importance of not limiting investigations to maternal factors, but rather making the investigation of attachment-related factors broader by assessing maternal, paternal and dyadic features.